Is there a hole in the topside, equatorial ionosphere? - D. Gallagher (Results in Physics, 2016)
A paper in 2000 (Huba, 2000) found a depression in electron density in the topside ionosphere near the magnetic equator, based on the SAMI-2 physical ionospheric model. The model showed, for the first time, the formation of a hole in electron density in the altitude range 1500–2500 km at geomagnetic equatorial latitudes. The model produced the hole because of transhemispheric O+ flows that collisionally couple to H+, transporting it to lower altitudes, and thereby reducing the electron density at high altitudes. At that time and until now, no published observations have been reported to confirm or refute this numerical result. Recent, new analysis of Dynamics Explorer 1 Retarding Ion Mass Spectrometer measurements provides the first tentative experimental support for this model result. Keywords: Ionosphere, Topside, Magnetic equator, Plasmasphere